Influences of prior miscarriage and weight status on perinatal psychological well-being, exercise motivation and behavior - Devlin, Courtenay A. (Midwifery, 2016)
OBJECTIVES: women who have experienced miscarriage may be at increased risk for elevated depressive and anxiety symptoms in subsequent pregnancies. Exercise may be a useful strategy for coping with these symptoms. Little is known about how miscarriage influences prenatal exercise behavior. The study purpose was to examine the influences of miscarriage history and prepregnancy weight status on pregnant women’s psychological health, exercise motivation, and behavior using the Theory of Planned Behavior. PARTICIPANTS/SETTING: Pregnant women (N=203; 41 with prior miscarriage; 72 overweight/obese; BMI > 25.0) in the northeast United States. DESIGN: Women prospectively reported their depressive/anxiety symptoms and exercise motivation/behavior in the 1st, 2nd, and 3rd trimesters via mailed surveys. Group differences in depressive/anxiety symptoms, exercise behavior, and its motivational determinants were examined using Chi Square analyses and Univariate and Multivariate Analyses of Covariance. MEASUREMENTS AND FINDINGS: Women with a history of miscarriage had higher 1st and 2nd trimester depressive/anxiety symptoms and lower 1st trimester attitudes about exercise and 1st and 2nd trimester perceived behavior control than women without a history of miscarriage. Overweight/obese women had higher 1st and 2nd trimester pregnancy depressive/anxiety symptoms, engaged in less prepregnancy exercise, and had lower levels of exercise intention, attitude, and perceived behavior control throughout pregnancy than normal weight women. KEY CONCLUSIONS: Women with a history of miscarriage and overweight/obese women have poorer psychological health and lower motivation to exercise during pregnancy than women without a history of miscarriage and normal weight women. IMPLICATIONS FOR PRACTITIONERS: Interventions and healthcare provider communications aimed at promoting perinatal exercise behavior and psychological health should take into account pre-pregnancy weight status and pregnancy history to identify strategies to help women, particularly overweight/obese women with a history of miscarriage, to overcome exercise barriers.